PENGGUNAAN MEDIA PEMBELAJARAN POSTER DI BENGKEL - Indah Wahyuni; Nur Hidayat (Universitas Negeri Yogyakarta, 2019)
ABSTRACTThis study is aimed to determine: (1) the use of posters as a medium of learning at the workshop of Education Department of Civil Engineering and Planning FT UNY, (2) requirements in making posters as instructional media, and (3) Correspondence between poster as a learning media with the workshop at Department of Education of Civil Engineering and Planning FT UNY. This study Applies a descriptive approach (descriptive research). In this study, the researchers did not provide any treatment to what is observed however only describes in detail merely to what was found in the data collection. The findings of this study are (1) poster has been used as a medium of learning both in carpentry, plumbing workshop, and rock workshop. Poster is used to convey information such as personal protective equipment, work step, parts of an instrument, learning products, and K3 (2) the factors of the preconditions if poster at carpentry and rock workshop have been fulfilled. However the preconditions the form of size and color of poster at the plumbing workshop still need to be resized. In addition, the suitability factors such as ease of posters indicators in order to be easily seen in carpentry and plumbing workshop also need to be resized. Other indicators contained in preconditions factors such as expediency and suitability in the third workshop have been fulfilled. (3) The compliance of poster in carpentry, plumbing workshop, and rock workshop at the Education Department of Civil Engineering and Planning FT UNY is good. Posters are suitable to the function and purpose of each workshop. They only need resizing and repositioning. Keywords: instructional media, posters, workshop ABSTRAKPenelitian ini bertujuan untuk mengetahui: (1) penggunaan poster sebagai media pembelajaran di bengkel Jurusan Pendidikan Teknik Sipil dan Perencanaan FT UNY (2) persyaratan dalam pembuatan poster sebagai media pembelajaran (3) Kesesuaian antara media pembelajaran poster dengan bengkel di Jurusan Pendidikan Teknik Sipil dan Perencanaan FT UNY. Penelitian ini menggunaan pendekatan deskriptif (descriptive reasearch). Dalam penelitian ini, peneliti tidak memberikan perlakuan terhadap apa yang diteliti tetapi hanya sebatas mendeskripsikan secara detail terhadap apa yang ditemukan dalam pengambilan data. Hasil penelitian ini adalah (1) Poster telah dimanfaatkan sebagai media pembelajaran baik di bengkel kayu, bengkel plambing, maupun bengkel batu. Poster digunakan untuk menyampaikan informasi alat pelindung diri, langkah kerja, bagian-bagian dari suatu alat, produk pembelajaran, maupun K3 (2) Faktor prasyarat poster di bengkel kayu dan bengkel batu sudah terpenuhi. Hanya saja untuk prasyarat berupa indikator ukuran dan warna poster di bengkel plambing masih perlu ditingkatkan. Selain itu, faktor kesesuaian berupa indikator kemudahan poster untuk terlihat di bengkel kayu dan plambing juga perlu ditingkatkan. Indikator lain yang terdapat pada faktor prasyarat, kemanfaatan, dan kesesuaian di ketiga bengkel tersebut sudah terpenuhi (3) Kesesuaian poster di bengkel kayu, bengkel plambing, dan bengkel batu di Jurusan Pendidikan Teknik Sipil dan Perencanaan FT UNY sudah baik. Poster sudah sesuai dengan fungsi dan maksud masing-masing bengkel. Hanya saja perlu adanya pembenahan dalam penempatan poster.Kata kunci: media pembelajaran, poster, bengkel